INTEGRATED MARKETING COMMUNICATIONS (IMC) STRATEGY IN ATTRACTING ATTENTION INTEREST BUY CONSUMERS IN THE CURRENT COFFEE BUSINESS - Muh. Husriadi; Ikrar Muadsim; Usman. M (Adisam Publisher, 2025)
Contemporary coffee industry the more competitive so it is important for business actors to implement effective marketing strategies use interesting interest buy consumers. This study aims to explore implementation of Integrated Marketing Communications (IMC) and its impact on consumer interest buy consumers in contemporary coffee businesses. The research method used is qualitative with interviews in-depth and focused group discussions to coffee shop owners and managers. The results of the study showed that the implementation of IMC through social media, promotion attractive and launching new menus can increase interest buy and create experience comprehensive for customers. However, challenges such as limited budget and difficulties guard consistency messages across multiple channels need to be addressed. The implications of this research suggest that an integrated IMC strategy can strengthen connection between brands and consumers as well as increase competitiveness in the market. This study also suggests further exploration of collaboration with local influencers to enhance effectiveness marketing.